Fatores determinantes da deambulação comunitária ilimitada em indivíduos após acidente vascular encefálico crônicos - Maria Tereza Mota Alvarenga (2021)
About 70-80% of individuals after stroke recovery to walk. Many studies with the objective of explaining unlimited community ambulation, represented by a gait speed greater than 0.8m/s, have already been carried out. However, none of them takes into account the maintenance of this gait speed for distances greater than ten meters, a necessary situation for unlimited community walking. Furthermore, most studies did not investigate the simultaneous contribution of variables that represent levels of body structure and function, activity and participation limitations, and personal factors to unlimited community ambulation. To examine which of motor impairments (muscular strength of the lower limbs, dynamic balance, and motor coordination of the lower limbs), activity limitations (capacity- and performance-based measures), and personal factor (self-efficacy) best explain unlimited-community ambulation in chronic stroke individuals. This was a cross-sectional and exploratory study, approved by the Institutional Committee of Ethics and Research of the University Federal of Minas Gerais, CAAE: 65765817.3.0000.5149. The sample was composed of chronic stroke individuals according to the following inclusion criteria: age ≥ 20 years, were at least six months after the onset of the stroke; could walk independently, and were not using any walking devices. The independent variables were: muscle strength of the lower limbs (hand-held dynamometer), dynamic balance (Four Step Square Test), motor coordination of the lower limbs (LEMOCOT), walking speed (10-meter walking speed test), self-perception of locomotion (ABILOCO) and self-efficacy in walking (Modified Gait Efficacy Scale). Unlimited-community ambulation was defined as the dependent variable and measured by the Six Minute Walking Test (6MWT). Those individuals who walked 288 meters or more were categorized as unlimited-community ambulators and those who walked less than 288 meters were categorized as limited-community ambulators. Binary logistic regression analysis was carried out to identify which variables could significantly explain the unlimited-community ambulation. An alpha value of 0.05 was adopted. 90 participants were included in the study. Of these, 51 (57%) were categorized as unlimited-community ambulators. The mean of age was 68 years (SD13) and mean time after stroke was 27 months (SD17). Binary logistic regression analysis showed that walking speed (p: 0.007; OR=59.09; 95% CI= 3.05- 1,144.32) and dynamic balance (p:0.008; OR=0.87; 95% CI= 0.78-0.96) best explain unlimited-community ambulation. Together, these variables explained 84% of the variation in community ambulation levels. Walking speed and dynamic balance showed to explain unlimited-community ambulation in chronic stroke individuals. Future studies are needed to determine whether rehabilitation interventions aiming at increasing walking speed and dynamic balance would lead to unlimited community ambulation in chronic stroke individuals.